Nutrition and production systems of the 'Bísaro' pig in the north-east region of Portugal - Martins de Carvalho M.A. (Tradition and innovation in Mediterranean pig production, 2000)
The main objective of this paper is to add to the store of knowledge on the alimentation and production systems of the 'Bísaro' race of pig in the North-east Transmontano region of Portugal. This study is intended to be applied to the entire population of breeders of the 'Bisaro' pig in the Northeast Transmontano region. The statistical sample taken covered 30 per cent of the breeders of the Bísaro race in a total of 169 animals, distributed in the following manner: 22 boars, 41 pregnant sows, one sow in lactation, 19 pigs for fattening, 44 weaned piglets and 42 suckling piglets. The field research was done between January and May 1997 and covered the following aspects: the composition and dimension of the pig population, reproduction, alimentation and management of the breeding animals, piglets and fattening pigs. The working tool used was the questionnaire.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)